Molecular biology - Weaver, Robert F. (McGraw Hill, 2008)
Molecular Biology, Fourth Edition" by Robert Weaver, is designed for an introductory course in molecular biology. The text is geared not only toward presenting concepts of molecular biology, but also the experiments that led to those concepts. Guided by this experimental approach, Dr. Weaver has been published by National Institutes as well as National Geographic